Caesarean Scar Ectopic Pregnancy Treated with local Methotrexate: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Ectopic pregnancy in a caesarean scar is the rarest form of ectopic pregnancy and probably the most dangerous one because of the risk of uterine rupture and massive hemorrhage. Since the advent of endovaginal ultrasonography, ectopic pregnancy in a caesarean scar can be diagnosed and distinguished from cervical pregnancy early in pregnancy. Here we describe a case of ectopic pregnancy in a caesarean scar in which the diagnosis was done at 6 weeks of pregnancy by transvaginal sonography and confirmed by MRI. The case was successfully managed by ultrasonography guided local injection of methotrexate into the gestational sac through trans abdominal route.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 43-48